The effects of exercise on mental health among college students - Takacs, Mark P.; Davis, Shala E.; Drago, Anthony; Beyer, Kyle S. (Health Promotion & Physical Activity, 2025)
Background: The prevalence of mental health (MH) disorders among college-aged young adults is alarmingly high, with many also experiencing poor physical health and comorbidities. The purpose of this study was to examine the effects of exercise on MH among college students. Materials and methods: Fifteen participants (60% males, 20.0 ± 2.0 years) participated in this 8-week study. Nine participants completed the exercise (EX) intervention, while 6 formed the non-exercise control (CON) group. The Depression Anxiety Stress Scores (DASS-21) instrument was used to collect data for the dependent variable and analyzed using linear mixed models (LMM). Results: No statistically significant differences were found in depression (F = 0.015, p = 0.904), anxiety (F = 1.038, p = 0.327), and overall MH (F = 0.266, p = 0.615) scores between groups or over time. The EX group’s pre/post scores (mean ± standard deviation) for depression (pre: 1.11 ± 2.62, post: 2.44 ± 5.34), anxiety (pre: 1.00 ± 0.87, post: 3.11 ± 2.52), and overall MH (pre: 3.33 ± 5.34, post: 8.55 ± 13.06). The CON group’s pre/post scores for depression (pre: 0.66 ± 1.21, post: 2.32 ± 3.83), anxiety (pre: 1.67 ± 2.40, post: 5.16 ± 6.49), and overall MH (pre: 4.33 ± 4.23, post: 13.33 ± 16.91). Conclusion: Although there were no statistically significant differences in depression, anxiety, and overall MH scores between the EX and CON groups, the findings may have practical implications. Notably, the anxiety and overall MH scores in the CON group exceeded the normal classification, and the EX group maintained normal scores throughout the 8-week intervention. These findings suggest that regular exercise likely plays a crucial role in sustaining MH status, highlighting its importance as a preventive measure rather than solely a therapeutic intervention.